Review of the Transition From Smouldering to Flaming Combustion in Wildfires - Santoso, Muhammad A.; Christensen, Eirik G.; Yang, Jiuling; Rein, Guillermo (Frontiers in Mechanical Engineering, 2019)
Wildfires are uncontrolled combustion events occurring in the natural environment (forest, grassland, or peatland). The frequency and size of these fires are expected to increase globally due to changes in climate, land use, and population movements, posing a significant threat to people, property, resources, and the environment. Wildfires can be broadly divided into two types: smouldering (heterogeneous combustion) and flaming (homogeneous combustion). Both are important in wildfires, and despite being fundamentally different, one can lead to the other. The smouldering-to-flaming (StF) transition is a quick initiation of homogeneous gas-phase ignition preceded by smouldering combustion, and is considered a threat because the following sudden increase in spread rate, power, and hazard. StF transition needs sufficient oxygen supply, heat generation, and pyrolysis gases. The unpredictable nature of the StF transition, both temporally and spatially, poses a challenge in wildfire prevention and mitigation. For example, a flaming fire may rekindle through the StF transition of an undetected smouldering fire or glowing embers. The current understanding of the mechanisms leading to the transition is poor and mostly limited to experiments with samples smaller than 1.2 m. Broadly, the literature has identified the two variables that govern this transition, i.e., oxygen supply and heat flux. Wind has competing effects by increasing the oxygen supply, but simultaneously increasing cooling. The permeability of a fuel and its ability to remain consolidated during burning has also been found to influence the transition. Permeability controls oxygen penetration into the fuel, and consolidation allows the formation of internal pores where StF can take place. Considering the high complexity of the StF transition problem, more studies are needed on different types of fuel, especially on wildland fuels because most studied materials are synthetic polymers. This paper synthesises the research, presents the various StF transition characteristics already in the literature, and identifies specific topics in need of further research.